Impact of Financial Literacy on Investment Decisions of Investors in Bhaktapur - Shrestha, Narayan Kumar; Gwachha, Babita (Community College Research Journal, 2025)
Financial literacy has gained critical importance in today’s rapidly evolving financial markets as it empowers individuals to make informed and effective investment decisions. This study aimed to assess the level of financial literacy among investors in Bhaktapur and examine its relationship and impact on their investment decisions. A quantitative approach was employed using descriptive and causal research designs. Out of 600 distributed structured questionnaires based on a five-point Likert scale, 489 valid responses were collected. Descriptive statistics (mean and standard deviation) were used to evaluate financial literacy levels, while correlation analysis assessed the relationships between financial literacy components and investment decisions. Linear regression analysis was applied to determine the influence of financial knowledge, financial behavior, and financial attitude on investment decisions. The findings revealed that investors in Bhaktapur exhibited moderate to high levels of financial literacy. A significant and positive relationship was observed between financial knowledge, financial behavior, and financial attitude with investment decision-making, and these factors were found to have a statistically significant positive impact. The study contributes to existing literature by providing empirical evidence on the role of financial literacy in investment decisions within a developing economy context. It also offers valuable implications for policymakers to design targeted financial education programs aimed at improving investor outcomes. However, the study’s scope was limited to Bhaktapur district and relied on self-reported data, which may introduce response bias. Future research is recommended to cover wider geographic regions, employ longitudinal and mixed-method approaches, and explore additional factors influencing investment decisions to enhance generalizability and depth of understanding.